Hubungan Suplemen Tablet Tambah Darah sebagai Pemenuhan Gizi Mikro Terhadap Potensi Stunting di Negara Indonesia; Tinjauan Sistematis Literatur - Zeni Dermawan; Indra Permana; Sri Setiatjahjati (Calory Journal Medical Laboratory Journal, 2025)
Background: Iron-containing blood-boosting tablet supplements are crucial for meeting micronutrient needs in pregnant women and children. Micronutrient deficiencies, such as iron, have the potential to cause stunting. This supplementation program is expected to improve the nutritional status of the Indonesian population, prevent stunting, and support optimal growth.Objective: This systematic literature review aims to analyze the relationship between iron-boosting tablet supplements in meeting micronutrient needs and preventing stunting in children (toddlers and infants) in Indonesia.Method: A systematic literature search was conducted to identify relevant articles in 3 main databases (Scopus, PubMed, and Google Scholars). Studies on the consumption of iron-boosting tablets for meeting micronutrient needs in stunting cases require a systematic review with inclusion criteria limited to articles published between 2015-2024, free full text, in Indonesian and English.Results: Of the 10 articles analyzed, most showed that consumption of Iron-Boosting Tablets (TTD) in pregnant women can increase hemoglobin levels and reduce the risk of anemia, which contributes to the prevention of stunting in children. However, the compliance rate of pregnant women in consuming TTD is still low due to side effects and lack of awareness. Additionally, socio-economic factors also play a role in children's nutritional status, where families with low incomes have a higher risk of anemia and stunting.Conclusion: TTD supplementation plays an important role in the prevention of anemia and stunting in children. However, its effectiveness is greatly influenced by the level of consumption compliance and socio-economic factors. Therefore, more intensive education and multi-sectoral policies are needed to improve accessibility and compliance with TTD consumption in stunting prevention efforts in Indonesia.